Usability and Acceptability of a Co-Designed Menstruation Tracker App for Indonesian Adolescent Girls - Arlyana Hikmanti; Martyarini Budi Setyawati (Journal of Advanced Health Informatics Research, 2026)
Background: Many adolescent girls experience limited access to accurate and age-appropriate menstrual health information, which may contribute to anxiety, stigma, and suboptimal menstrual hygiene practices. Existing menstrual tracking applications are often designed for adult users and may not address adolescent needs in local cultural contexts. Objective: This study evaluated the perceived usability and acceptability of Srikandi Sehat, a co-designed menstruation tracker application for Indonesian adolescent girls. Method: A prospective usability evaluation was conducted among 151 adolescent girls aged 13-18 years who used the application during three menstrual cycles. The application was developed through a co-design process involving adolescent users and health workers. Data were collected using electronic questionnaires on menstrual knowledge, technology-related attitudes, and application usability. Descriptive statistics and Spearman correlation analyses were used because knowledge and usability scores were not normally distributed. Results: The modified usability scale showed a mean total score of 133.35 out of 160 (SD 19.72), indicating favorable perceived usability within the scoring framework used in this study. Participants reported that the application was easy to navigate, visually understandable, age-appropriate, and useful for recording menstrual cycles and symptoms. Attitude toward menstrual health showed a stronger association with usability (rho approximately 0.53, p < 0.001) than knowledge (rho approximately 0.21, p = 0.010). These findings indicate association rather than causation. Conclusion: Srikandi Sehat was perceived as usable and acceptable by participating adolescent girls. Further studies should validate the adapted instruments, include objective usage analytics, and evaluate educational or behavioral outcomes using controlled and longer-term designs.